Fibroblast growth factor receptor 1 5-hydroxytryptamine 1A heteroreceptor complexes and their enhancement of hippocampal plasticity - Borroto-Escuela, Dasiel O.; Romero-Fernandez, Wilber; Mudó, Giuseppa; Pérez-Alea, Mileidys; Ciruela, Francisco; Tarakanov, Alexander O.; Narvaez, Manuel; Di Liberto, Valentina; Agnati, Luigi F.; Belluardo, Natale; Fuxe, Kjell (Elsevier, 2012)
Background: The hippocampus and its 5-hydroxytryptamine transmission plays an important role in depression related to its involvement in limbic circuit plasticity. Methods: The analysis was made with bioluminescence resonance energy transfer, co-immunoprecipitation, in situ proximity ligation assay, binding assay, in cell western and the forced swim test. Results: Using bioluminescence resonance energy transfer analysis, fibroblast growth factor receptor 1 (FGFR1)-5-hydroxytryptamine 1A (5-HT1A) receptor complexes have been demonstrated and their specificity and agonist modulation characterized. Their presence based on co-immunoprecipitation and proximity ligation assay has also been indicated in hippocampal cultures and rat dorsal hippocampal formation showing a neuronal location. In vitro assays on extracellular signal-regulated kinases 1 and 2 phosphorylation have shown synergistic increases in signaling on coactivation with fibroblast growth factor 2 (FGF2) and a 5-HT1A agonist, and dependent on the heteroreceptor interface. In vitro and in vivo studies also revealed a 5-HT1A agonist induced phosphorylation of FGFR1 and extracellular signal-regulated kinase 1/2 in rat hippocampus without changing FGF2 levels. Co-activation of the heteroreceptor also resulted in synergistic increases in extensions of PC12 cells and neurite densities and protrusions in primary hippocampal cultures dependent on the receptor interface. The combined acute and repeated intracerebroventricular treatment with FGF2 and 8-OH-DPAT was found to produce evidence of highly significant antidepressant actions in the forced swim test. Conclusions: The findings indicate that neurotrophic and antidepressant effects of 5-HT in brain may, in part, be mediated by activation of the 5-HT1A receptor protomer in the hippocampal FGFR15-HT1A receptor complex enhancing the FGFR1 signaling.
Keywords: Serotonina - Receptores; Depresión; Receptores; Allosteric modulation; Depression; Fibroblast growth factor receptor; Heteroreceptor; Neuronal plasticity; Serotonin receptors